Percutaneous vacuum-assisted tumor thrombectomy using angiovac and penumbra lightning 12 aspiration systems - Murtaza Jafri, BSc; Brittany Stojak, MD; Owen Mooney, MD; Andrew Macdiarmid, MD; Ian W. Gibson, MD; Surinder Dhaliwal, MD (Radiology Case Reports)
A 19-year-old female presented with a 2-month history of abdominal discomfort and palpable abdominal mass; a computer tomography scan revealed a large retroperitoneal mass as well as high suspicion of thrombus in her inferior vena cava. Right kidney core biopsy showed diagnostic features of synovial sarcoma. While awaiting workup for her mass she was placed on anticoagulants. However, she re-presented to hospital 3 weeks later complaining of 3 days of shortness of breath. A repeat computer tomography scan revealed extensive thrombus burden with tumor thrombus involving the inferior vena cava, a large right atrial intracardiac thrombus, multiple segmental right pulmonary emboli, and a large embolus causing total occlusion of the left main pulmonary artery with findings suggestive of associated lung infarction. The patient's disease was not amenable to surgical resection and thrombolytic therapy was contraindicated due to associated intratumor hemorrhage, thus prompting consideration of thrombectomy under emergency approval from Health Canada. The patient underwent an overall successful total aspiration thrombectomy of the intracardiac tumor thrombus with subsequent resolution of her right heart strain, using the extracorporeal AngioVac aspiration system and partial aspiration of the extensive pulmonary emboli using the Penumbra Indigo Lightning 12 system. She was transferred to the intensive care unit and extubated 2 days later and was discharged from hospital shortly after without supplemental oxygen.